Ultrasensitive Detection of Chimerism by Single-Molecule Molecular Inversion Probe Capture and High-Throughput Sequencing of Copy Number Deletion Polymorphisms - Wu, David; Waalkes, Adam; Penewit, Kelsi; Salipante, Stephen J (Clinical chemistry (Baltimore, Md.), 2018)
Genomic chimerism, the co-occurrence of cells from different genetic origins, provides important diagnostic information in diverse clinical contexts, including graft injury detection and longitudinal surveillance of hematopoietic stem cell transplantation patients, but existing assays are limiting. Here we applied single-molecule molecular inversion probes (smMIPs), a high-throughput sequencing technology combining multiplexed target capture with read quantification mediated by unique molecular identifiers, to detect chimerism based on the presence or absence of polymorphic genomic loci. We designed a 159-smMIP panel targeting 40 autosomal regions of frequent homozygous deletion across human populations and 2 sex-linked loci. We developed methods for detecting and quantitating loci absent from 1 cell population but present in another, which could be used to sensitively identify chimeric cell populations. Unrelated individuals and first-degree relatives were highly polymorphic across the loci examined. Using synthetic DNA mixtures, limits of detection of at least 1 in 10000 chimeric cells were demonstrated without prior knowledge of genotypes, and mixtures of up to 4 separate donors could be deconvoluted. Quantitative linearity over 4 orders of magnitude and false-positive rates <1 in 85000 events were achieved. Eleven of 11 posttransplant clinical specimens from patients with hematological malignancies testing positive for residual cancer by conventional methods had detectable chimeric populations by smMIP, whereas 11 of 11 specimens testing negative by conventional methods were low-positive for chimerism by smMIP. smMIPs are scalable to high sensitivity and large numbers of informative markers, enabling ultrasensitive chimerism detection for many clinical purposes.